Energy and exergy analysis of fuel cells: A review. (March 2019) - Arshad, Adeel; Ali, Hafiz Muhammad; Habib, Arslan; Bashir, Muhammad Anser; Jabbal, Mark; Yan, Yuying
Highlights: Physical concept of energy and exergy analysis is described. The fundamental thermodynamic governing equations of energy and exergy analysis are presented. Exergy analysis of flow and non-flow systems are covered. Energy and exergy efficiencies, analysis procedure, reference environment and models are discussed. Energy and exergy analysis of PEM, SOFC and MCFC fuel cells are covered in detail. Abstract: In this paper, the fundamental overview of theoretical and practical aspects of thermodynamics analysis for mainly used fuel cells (FCs) are presented. The FC converts the chemical energy of fuel (normally hydrogen) directly into electrical energy resulting heat and liquid water as a waste products. In first part, governing equation of mass, energy, entropy and exergy are presented according to first law of thermodynamics (FLT) and second law of thermodynamics (SLT), more specifically energy and exergy analysis are covered for fuel cell system. Basic criteria of energy and exergy analysis of flowing and non-flowing system, energy and exergy efficiencies, analysis procedure and models of reference environment are discussed in detail. In the second part, electrochemical reactions and thermodynamics modeling of proton exchange membrane or polymer electrolyte membrane fuel cell (PEMFC), solid oxide fuel cell (SOFC), and molten carbonate fuel cell (MCFC) are presented.